Red blood cell distribution width an inflammatory biomarker related to proliferative diabetic retinopathy - Roque, Juan Carlos (2020)
Objective: The aim of this study was to determine the association between Red Blood cell Distribution width and Proliferative Diabetic Retinopathy in patients with type 2 diabetes. Methods: We conducted a hospital-based case-control study. Adult patients (≥ 18 years old) with the diagnosis of Diabetic Retinopathy who underwent medical check-ups at the ophthalmology department where enrolled in our study. We selected a total sample size of 262 patients, of which 131 cases had Proliferative Diabetic Retinopathy and 131 controls had Non Proliferative Diabetic Retinopathy. Data about age, gender, body mass index, history of hypertension, diabetic nephropathy, Congestive heart failure, Hemoglobin and HbA1c were registered for individuals who met inclusion criteria. Odds ratio model was used to test the relationship between Red Blood Cell Distribution Width and Proliferative Diabetic Retinopathy. Results: Mean Red Blood cell Distribution width +/- SD of the cases was 14.41+/-0.84 and the controls was 13.49+/-1.26. According to bivariate analysis, an association was found between Red Blood cell Distribution width and Proliferative Diabetic Retinopathy (OR 3.79, P=0.000, IC=2.12-6.78). Multivariate logistic regression analysis indicated that Red Blood cell Distribution width (OR 2.15, P=0.037, IC= 1.05-4.43) was an independent risk factors for the development of Proliferative Diabetic Retinopathy. Conclusion: Elevated values of Red Blood cell Distribution width were related to Proliferative Diabetic Retinopathy, suggesting the potential application of Red Blood cell Distribution width as an accessible predictive biomarker of disease progression in patients with diabetic retinopathy.